Anglų kalbos gramatinė interferencija Šiaurės Amerikos lietuvių kalboje - Pažūsis, L. (Kalbotyra, 1976)
An attempt has been made to give a brief account of the grammatical interference of English in the Lithuanian immigrant language in North America. The transfer of English bound morphemes (such as inflectional endings, affixes, articles, prepositions) is not attested. The analysis is confined to the two types of grammatical interference: (1) the application of a grammatical relation of English to Lithuanian morphemes, or the neglect of a relation of Lithuanian which has no prototype in English, (2) through the identification of a specific Lithuanian morpheme with a specific English morpheme, a change (extension) in the functions of the Lithuanian morpheme on the model of the grammar of English (U. Weinreich).